MANAJEMEN PENANGANAN HEWAN LIAR (WILDLIFE HAZARD) TERHADAP KESELAMATAN PENERBANGAN DI PERUM LPPNPI CABANG PEMBANTU SAMARINDA - Aswiratin, Carolina Andini; Saulina, Martha (Politeknik Penerbangan Surabaya, 2025)
The research was carried out at Aji Pangeran Tumenggung Pranoto Samarinda International Airport to find out how the treatment of the existence of wild animals (dogs) affects aviation safety. In this study, a qualitative descriptive approach is used. From December 2020 to February 2021, direct field observations and documentation studies were used to collect data. The results of the research showed that the presence of wild animals entering the manouevering area and movement area often impeded the movement of aircraft. There needs to be special attention must be taken in the handling of wild animals to enhance flight safety at at Aji Pangeran Tumenggung Pranoto Samarinda International Airport. In addition, coordination and management system is needed, such as the establishment of wildlife prevention teams and infrastructure repairs that can be gaps for wildlife entry into manouevering areas and movement areas.